Draft Genome Sequence of Rickettsia sp. Strain MEAM1, Isolated from the Whitefly Bemisia tabaci - Rao, Qiong (American Society for Microbiology, 2012)
We report the draft genome sequence of the Rickettsia sp. strain MEAM1, which is a facultative symbiont from an invasive species of the whitefly Bemisia tabaci. The total length of the assembled genome is approximately 1.24 Mb, with 335 scaffolds and 1,247 coding sequences predicted within the genome.